Contrast-enhanced ultrasound of hepatocellular carcinoma: where do we stand? - Bartolotta, Tommaso Vincenzo; Taibbi, Adele; Midiri, Massimo; Lagalla, Roberto (Ultrasonography (Seoul, Korea), 2019)
Contrast-enhanced ultrasound (CEUS) represents a significant breakthrough in ultrasonography (US), and it is being increasingly used for the evaluation of focal liver lesions (FLLs). CEUS is unique in that it allows non-invasively assessment of liver perfusion in real time throughout the vascular phase, which has led to dramatic improvements in the diagnostic accuracy of US in the detection and characterization of FLLs, the choice of therapeutic procedures, and the evaluation of response. Currently, CEUS is included as a part of the suggested diagnostic work-up of FLLs, including in cirrhotic patients with hepatocellular carcinoma, resulting in better patient management and cost-effective delivery of therapy.